Plan de marketing en la empresa “Victor Hugo” ubicada en la ciudad de Babahoyo - Rivera Plúas, Joel Ronny (2023)
The “Víctor Hugo” washing machine and lubricator is a business in the city of Babahoyo with eight years in the market specializing in automotive services such as washing, lubrication and maintenance. Lack of marketing strategies in the business have led to limited presence in the market. The main objective of this investigative work is to diagnose a marketing plan that helps the business address challenges, identify current strategies, and customer satisfaction, all with the aim of contributing to the success and positioning of the company. The “Víctor Hugo” washing machine and lubricator needs a clear approach to increase visibility and competitiveness in the automotive market; A marketing plan that adapts to changing market needs, promotes customer loyalty and creating a quality image at the same time are key factors. To diagnose the marketing plan, a situational evaluation of the company was carried out through SWOT, such as strengths, weaknesses, opportunities and threats, highlighting that it has a strategic location, trained personnel and a wide range of services. A survey was carried out on clients in which it was found that the majority were satisfied with the services, treatment and competitive prices they offer. They also highlighted the importance of social media advertising, which is key to attracting potential clients. The conclusions are highlighted in implementing a comprehensive and digital marketing plan to take advantage of opportunities and strengths, address weaknesses and work on threats, therefore, it will help improve the visibility of the business, achieve the goals and objectives set.